Reconstituting neurovascular unit with primary neural stem cells and brain microvascular endothelial cells in three‐dimensional matrix. (12th February 2021) - Wang, Hongjin; Yang, Huan; Shi, Yuhong; Xiao, Yaping; Yin, Yue; Jiang, Baoxiang; Ren, Huijing; Chen, Weihai; Xue, Qiang; Xu, Xiaoyu
Abstract: Neurovascular dysfunction is a primary or secondary cause in the pathogenesis of several cerebrovascular and neurodegenerative disorders, including stroke. Therefore, the overall protection of the neurovascular unit (NVU) is a promising therapeutic strategy for various neurovascular diseases. However, the complexity of the NVU limits the study of the pathological mechanisms of neurovascular dysfunction. Reconstituting the in vitro NVU is important for the pathological study and drug screening of neurovascular diseases. In this study, we generated a spontaneously assembled three‐dimensional NVU (3D NVU) by employing the primary neural stem cells and brain microvascular endothelial cells in a Matrigel extracellular matrix platform. This novel model exhibits the fundamental structures and features of the NVU, including neurons, astrocytes, oligodendrocytes, vascular‐like structures, and blood–brain barrier‐like characteristics. Additionally, under oxygen‐glucose deprivation, the 3D NVU exhibits the neurovascular‐ or oxidative stress‐related pathological characteristics of cerebral ischemia and the injuries can be mitigated, respectively, by supplementing with the vascular endothelial growth factor or edaravone, which demonstrated that the availability of 3D NVU in ischemic stroke modeling. Finally, the 3D NVU promoted the angiogenesis and neurogenesis in the brain of cerebral ischemia rats. We expect that the proposed in vitro 3D NVU model will be widely used to investigate the relationships between angiogenesis and neurogenesis and to study the pathology and pharmacology of neurovascular diseases. Abstract : The proposed 3D NVU model provides a valuable platform and precise spatiotemporal control for neurogenesis and angiogenesis research and the investigation of brain functions, which rely on interactions among brain cells, drug screening studies as a therapeutic strategy, and clinical applications (e.g., in the case of degenerative disease).